Sulfated polysaccharides from red seaweed Gelidium amansii: Structural characteristics, anti-oxidant and anti-glycation properties, and development of bioactive films. (October 2021) - Yu, Gang; Zhang, Qiaozhi; Wang, Yanbo; Yang, Qing; Yu, Hejun; Li, Huan; Chen, Jian; Fu, Linglin
Abstract: Marine red algae are rich sources of sulfated polysaccharides as bioactive ingredients and hydrocolloid molecules. In this study, sulfated polysaccharides (YGAP, EGAP, and NGAP) were extracted from Gelidium amansii s that were harvested from three different sea areas of China. Characterization of these polysaccharides shows that they contain 3.7–4.0% sulfate and are mainly composed of galactose, glucose, fucose, arabinose, and mannose. The FT-IR and 13 C NMR analysis indicate that the sulfated polysaccharides are agar-type galactans containing 3, 6 anhydro-α-l -galactopyranose and β-d -galactopyranose residues. By using various in vitro models, all sulfated polysaccharides, particularly EGAP, exhibit the ability to scavenge O2 – and OH· radicals and reducing power. Additionally, in a glucose-glycated BSA system, the polysaccharides show an inhibitory effect on protein glycation and formation of specific advanced glycation end-product. Their anti-glycative property is attributed to their anti-oxidant activity and trapping capacity of methylglyoxal. Given that these polysaccharides possess agar-like structures, they were used to prepare bioactive films and expectedly, transparent and homogeneous films were obtained. The films display high water barrier properties with retained antioxidant and anti-glycation activities as above. These results expand the current knowledge of G. amansii s polysaccharides as nutraceuticals and hydrocolloids, which would benefit their applications in the food industry. Graphical abstract: Image 1 Highlights: Polysaccharides are prepared from G. amansii harvested in three sea areas. Sulfated polysaccharides from G. amansii are characterized as agar-type galactans. G. amansii polysaccharides showed dual effects against oxidation and glycation. G. amansii polysaccharides exhibited dicarbonyl-trapping capacities. Produced films showed high water barrier properties with retained bioactivity.